A sensitive cataluminescence-based sensor using a SrCO3/graphene composite for n-propanol. Issue 71 (2nd August 2015) - Zhang, Qianchun; Meng, Feifei; Zha, Lin; Wang, Xingyi; Zhang, Guoyi
<x xml:space="preserve">Abstract</x> Adding graphene to SrCO3 enhanced the CTL intensity of n-propanol, and the SrCO3/graphene composite was used for sensitive detection of n-propanol.